Comparison of 15–20 mmHg versus 20–30 mmHg Compression Stockings in Reducing Occupational Oedema in Standing and Seated Healthy Individuals - Cleusa Ema Quilici Belczak; José Maria Pereira de Godoy; Amélia Cristina Seidel; Sergio Belczak; Rubiana Neves Ramos; Roberto Augusto Caffaro (International Journal of Vascular Medicine)
Background. Elastic compression stockings (ECS) are effective in preventing and reducing occupational edema (OE), but the optimal pressure according to the prevalent working position during the day is still controversial. Objective. To compare the effectiveness of ECS with different pressures (15–20 mmHg or 20–30 mmHg) for reducing OE in individuals working in different prolonged postures. Methods. This cross-sectional study comprised 116 lower limbs of 58 individuals divided into three groups according to their prevalent postures over the day (sitting, standing, or combination). Volumetric measurements were taken at the beginning and at the end of three consecutive days. On the first day, individuals did not use compression stockings; on the second and third days, they used, respectively, 15–20 mmHg and 20–30 mmHg knee-length stockings. Differences between morning and evening volumes (measured edema) were calculated, compared, and correlated. Results. Volumetric variations were significantly lower on the second compared to the first day when individuals in all three groups used 15–20 mmHg compression stockings (p-value < 0.001). Measurements were even lower when they used 20–30 mmHg stockings: this decrease was more significant for the sitting (p-value < 0.001) than the standing (p-value < 0.05) and combined groups (p-value < 0.05). Reduction of measured edema was more significant in individuals working in a prolonged seated position. No significant difference was found only on comparing sitting and standing groups after the use of the 15–20 mmHg compression stockings. Conclusions. The use of ECS over a working day reduces OE in prolonged sitting, standing, and combined positions, with the reductions being greater with the higher pressure.